The Fate of Persistent Organic Pollutants in the Environment - Mehmetli, Ebru.; Koumanova, Bogdana; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Persistent organic pollutants (POPs) are organic compounds of natural or anthropogenic origin that resist photolytic, chemical and biological degradation. They are characterized by low water solubility and high lipid solubility, resulting in bioaccumulation in fatty tissues of living organisms. These properties of unusual high persistence and semi-volatility, coupled with other characteristics, have resulted in the presence of POPs all over the world, even in regions where they have never been used. With the evidence of long-range transport of these substances to regions, the international community has now, at several occasions called for urgent global actions to reduce and eliminate releases of these chemicals. Many countries have already banned or severely restricted the production and use of the twelve POPs in recent decades. Yet they remain a serious problem around the world. Because these chemicals have the ability to travel long distances from their original sources, relying on national-level action alone is ultimately a futile effort. This book employs a science-based approach to identify and take action against POPs, and additionally, provides access to technical information on POPs. The book will be an overview of the existing POP monitoring activities and programs.
Regulatory Aspects -- Stockholm Convention on Pops: Obligations and Implementation -- Persistent Organic Pollutants (Pops) in the Republic of Moldova: Problems and Solutions -- Stockholm convention and current situation on pops in turkey -- Lessons Learned and Good Practice in the Preparation of the National Implementation Plan (NIP) for the Management of Pops in the Republic of Bulgaria -- Problem of Pops Management in Ukraine: the Lack of Interdepartmental Cooperation and Public Involvement -- Persistent Organic Pollutants (Pops) Management in Georgia -- Monitoring Activities and Current Situation -- Monitoring of Dioxins and Dioxin-Like Pcbs in Food, Feed, and Biological Samples in Greece -- Environmental Fate of Legacy Chiral Pesticides in Background Soils -- Persistent Organic Pollutants (POPs) Hot Spots in Russia -- Pcb Pollution of Izmit bay (Marmara sea) Mussels After the Earthquake -- Inventory of Unintentional Releases of Pops in Belarus -- Polychlorinated Biphenyls (Pcbs) in Belarus: Inventory and Priorities for Ecologically Sound Management -- The Fate of Persistent Organic Pollutants (Pops) in the Environment -- Persistent Organic Pollutants (POPs): Food Safety Control in Estonia -- Sources, Release Pathways, Fate, and Transport -- Analyzing the Global Fractionation of Persistent Organic Pollutants (Pops) -- Effect of Catastrophic Floods on the Spatial Distribution and Vertical Migration of Pahs in Soil of Flooded Areas -- Spatial and temporal trends of global, regional, and local pops distribution -- Halogenated Flame Retardants as Sources for Pops in the Environment -- Distribution of POPs in Aquatic Ecosystems and Processes for their Removal -- Variations of Organochlorine Contaminants in Antarctica -- Dioxin Characterisation, Formation, And Minimisation -- Occurrence, Fate, and Behavior of Brominated Flame Retardants in Ebro River Basin (Spain) -- Milk Contamination from Dioxins in Italy: Source Identification and Intervention Strategies -- Persistent Organic Pollutants (Pops) and Air$1 (BSoil Exchange: Case Studies for Ddts -- Partitioning and Exchange of Organochlorine Contaminants between Abiotic Compartments in Antarctica -- Remediation Methods -- Remediation of contaminated soils and water with organic chemicals by means of natural, anionic and organic clays -- The Role of Natural Organic Matter (Humic Substances) on Adsorption of Pesticides Possessing Endocrine Disruptor Activity -- Health Effects -- Pcb-contaminated areas in kazakhstan and analysis of pcb impact on human health experience -- Impact of pops on the republic of moldova environment and public health -- Persistent Organic Pollutants (Pops) at Nanotechnology and their Impact on People Health -- Preliminary Assessment of Situation Related to Dioxins and Furans Releases in Kazakhstan -- Advances in the Measurement of Pops -- Determination of Polybrominated Diphenyl Ethers (Pbdes) as Persistent Organic Pollutants (Pops) in Polish Food Using Semipermeable Membranes (Spms).s
Keywords: Environment; Environmental sciences; Ecotoxicology; Pollution; Environment; Pollution, general; Environmental Science and Engineering; Ecotoxicology; Electronic books